Mechanism and kinetics of the α–β transition in San Carlos olivine Mg1.8Fe0.2SiO4. Issue 1 (31st January 2013) - Perrillat, J. P.; Daniel, I.; Bolfan‐Casanova, N.; Chollet, M.; Morard, G.; Mezouar, M.
Abstract : [1] The mechanism and kinetics of the α–β transformation in San Carlos olivine α‐Mg1.8 Fe0.2 SiO4 containing ca. 526 wt.ppm H2 O were studied in situ by time‐resolved synchrotron X‐ray diffraction (XRD) in the range 12.5 – 14.5 GPa and 870 – 1150 K. Time series of XRD spectra reveal the early formation of an intermediate phase that further transforms to wadsleyite (β‐phase). This intermediate phase may be either a metastable ringwoodite (γ‐phase) or the disordered spinelloid phase proposed in the pseudomartensitic reaction model. Both microstructural and kinetic data suggest that the transformation rates are controlled by growth processes after the early saturation of nucleation sites along olivine grain boundaries. Growth rates in the range 1.7×10 −12 – 2.1×10 −9 m.s −1 are estimated by fitting the transformation–time data to the Cahn rate equation and define an activation enthalpy for growth ΔHa = 204(55) kJ/mol. Compared to the previous studies performed on pure forsterite Mg2 SiO4, these new kinetic results point out an increase of transformation rates with the iron content. Hence, the persistence of a metastable olivine wedge to depths > 660 km might be restricted to even colder and/or dryer subduction zones than previously estimated. Key Points: Experimental data on the kinetics of the a‐b reaction in olivine Transformation rates increase with increasing iron content Implications for the metastability of olivine in subduction zones